Filtration membrane technology for water treatment - Lee, Esther Swin Hui. (2008)
Membrane technology is currently the treatment technology of preference because it is both cost-competitive with conventional treatment methods and produces clean water that meets all primary and secondary water standards. On the other hand, the Safe Drinking Water Act (SDWA) and its amendments also have a dramatic impact on the way in which how the treatment and distribution of water is viewed nowadays. Currently, out of the low-pressure full-scale plants identified worldwide, ultrafiltration (UF) applications represent about 74% of the total installed capacity. Today, UF technology is being used worldwide for treating various water sources. In this dissertation, a literature review on membrane filtration was conducted. An introduction to membrane technology and its classification were presented. Membrane fouling, the advantages and disadvantages of the membrane technology were discussed. On the other hand, the applications of membrane technology for water treatment were introduced.